การประเมิน cerebrovascular reserve ในผู้ป่วย chronic cerebrovascular insufficiency โดยการใช้ resting state hemodynamic parameter - อริยประกาย ชานน; ศรีอมรรัตนกุล กิติพร; อัครธรรมโชติ นาแสง; วงศ์สุริยนันท์ สมเกียรติ (Thai Journal of Neurological Surgery, 2025)
Cerebrovascular reserve (CVR) is an important hemodynamic parameter for evaluating patients with chronic cerebrovascular insufficiency regarding both treatment options and long-term prognosis. Acetazolamide challenge test and CO2 inhalation test are standard methods for CVR evaluation. However, both methods have several complications and limitations. Indirect measurement of CVR by resting hemodynamic parameter is an alternative diagnostic tool especially in the center where direct CVR measurements are unavailable. In this article, we review literatures that compare resting hemodynamic parameters to direct measurement of CVR. We found that among resting hemodynamic parameters including mean transit time (MTT), cerebral blood flow (CBF), and cerebral blood volume (CBV), only mean transit time (MTT) is significantly correlated with direct measurement of CVR.